The unemployment rate and the future of the employment market in Romania The impact of inflation A study on the Romanian post-pandemic economy dominated by uncertainty - Maria GHEORGHE; Aureliana ROMAN (Theoretical and Applied Economics, 2024)

(untitled)
This study was conducted to understand the fluctuation of the unemployment rate and the inflation rate in Romania in the post-pandemic years. Also, the study aims to highlight the future of these two variables based on the forecasted values, but also on the possible future state of the economical and geopolitical framework. For this purpose, the correlation between the inflation and unemployment rate in the last 4 years in Romania is going to be analyzed using a linear regression model. Based on the output of the model, a series of conclusions is going to be highlighted related to the impact of the inflation rate on the fluctuation of the unemployment rate in the post-pandemic period (2020-2023). The research will indicate that there is still a strong correlation between the two variables and that a high percentage (more than 91%) of the fluctuation of the unemployment rate in Romania in the post-pandemic years is explained by the fluctuation on the inflation rate.